Development of Mouthwash Formulations based on Natural Ingredients with Antimicrobial Activity - Adelia Y. P. Hasibuan; Harry Agusnar; Muhammad Taufik (Jurnal Akademika Kimia, 2022)
Dental and oral health problems are one of the problems that need attention. The oral cavity is colonized by various microflora and some bacteria, so it is necessary to develop additional oral cleaning methods besides brushing teeth. Mouthwash with natural ingredients, such as a combination of chitosan and Eucalyptus grandis, is the right choice. Chitosan is a type of water-soluble chitosan characterized using FT-IR. Meanwhile, Eucalyptus grandis was isolated using the Stahl method to obtain its essential oil. Mouthwash was evaluated through organoleptic testing, pH, viscosity, and antimicrobial testing. The most optimal formula is formula III, with an inhibition zone diameter of 11.9 ± 1.5 mm for Streptococcus mutans bacteria, 12.8 ± 0.9 mm for Staphylococcus aureus, and 12.2 ± 0.15 mm for Candida albicans.